Quincas Borba: da Megalomania à Decadência - Soares, Rogério de Nazareth (2019)
The present dissertation proposes to study the interfaces of politics in Quincas Borba, Machado de Assis. For this reason, the research is based on: a) John Gledson's analysis of Quincas Borba found in the book Machado de Assis: fiction and history, in which the critic points out, from the modifications made by the author in the final book edition (1891) an allegory of the end of the Second Kingdom; b) Raymundo Faoro's studies in Machado de Assis: The pyramid and the trapeze, where situations and circumstances involving the political theme in the work of the author of Dom Casmurro are punctuated and analyzed; c) Brito Broca's contribution to Machado de Assis and politics, in which the critic presents the political universe in Machado's work, in order to analyze how the "extraordinary human spectacle" occurs in the arteries of literature and also in the Brazilian imperial reality ; d) and, finally, the investigations of Lilia Moritz Schwarcz on Dom Pedro II and the Second Reign in The beards of the emperor: a monarch in the tropics. In this sense, three characters that situate the political sphere of the novel will be analyzed: Rubião, Camacho and Teófilo. In the case of Pedro Rubião, the study will be constituted in the relation between megalomania and its consequent decay. For the madness of the protagonist can function as a mediator in order to diagnose the tense political moment of July 1868, when the emperor overthrows a liberal cabinet and replaces it with a conservative. Such an act culminated in the collapse of the monarchy. Thus, it is intended to present as a result in the dissertation, a study of politics between the years 1867-1871 under the veins of literature, and how madness mediates the megalomania and decadence of Rubião and the Brazilian Empire.